A Qualitative Study of Arab-American Perspectives on Intimate Partner Violence in Dearborn, Michigan. (August 2022) - Khan, Angubeen G.; Eid, Neda; Baddah, Lama; Elabed, Layla; Makki, Mona; Tariq, Madiha; King, Elizabeth J.; Kusunoki, Yasamin
Few studies explore how intimate partner violence (IPV) affects Arab Americans. Through focus groups with stakeholders from an Arab-centered health organization and semistructured interviews with Arab-American female clients (18–65 years), we explore how IPV affects Arab-American women and factors that impede and facilitate their access to support services. We find that IPV is a critical concern among Arab Americans and that generational status, educational attainment, and support from family, friends, or religious leaders were perceived to influence access to IPV support services. This study has implications for developing culturally sensitive IPV interventions for Arab-American women.